1921 Ga. Laws 95-97 - (:unkn) unknown (My University, 1921)
Taxation, § 1087: Required the Receiver of Tax Returns to have a full and correct return on the value of guns, pistols, Bowie-knives, and "such articles."
Keywords: TAX - PROPERTY OR SALES